2017
DOI: 10.1175/jcli-d-16-0535.1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Associated with Convergence Lines

Abstract: Precipitation is often organized along coherent lines of low-level convergence, which at longer time and space scales form well-known convergence zones over the world’s oceans. Here, an automated, objective method is used to identify instantaneous low-level convergence lines in reanalysis data and calculate their frequency for the period 1979–2013. Identified convergence lines are combined with precipitation observations to assess the extent to which precipitation around the globe is associated with convergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…We then apply the regression model using the occurrence and strength of the convergence lines to both observations and GCMs to estimate the precipitation at each point. The slight overestimation of the reconstructed precipitation (Figures 2c and 2d) is partly because some convergence lines are dry Weller, Shelton, et al, 2017). We find that the proportion of the precipitation associated with convergence lines can be faithfully reconstructed (Figures 2a and 2b) with large errors confined to regions away from the major convergence zones where the mean precipitation is small.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…We then apply the regression model using the occurrence and strength of the convergence lines to both observations and GCMs to estimate the precipitation at each point. The slight overestimation of the reconstructed precipitation (Figures 2c and 2d) is partly because some convergence lines are dry Weller, Shelton, et al, 2017). We find that the proportion of the precipitation associated with convergence lines can be faithfully reconstructed (Figures 2a and 2b) with large errors confined to regions away from the major convergence zones where the mean precipitation is small.…”
Section: Resultsmentioning
confidence: 71%
“…Once the convergence lines are identified, they are associated with the National Oceanic and Atmospheric Administration/Climate Prediction Center morphing technique (CMORPH; Joyce et al, 2004) 6-hourly accumulated precipitation when a convergence line is found sufficiently close (i.e., adjacent grid points) to the precipitation grid point (see Weller, Shelton, et al (2017) for details). It is noted that ERA-Interim winds are often based on relatively few observations over the tropics, and therefore, the degree to which they represent reality is uncertain.…”
Section: Observation-based Convergence Lines and Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a second important step, precipitation is associated with the objectively identified convergence lines when they are found to be close to each other for each 6‐hourly field (see Weller et al, for details). In the current study, adjacent grid points (±1 grid point in size) are searched for an identified convergence line for each rain grid point to account for all the precipitation that may be related to the broader system associated with a convergence line.…”
Section: Methods and Datamentioning
confidence: 99%